2019
DOI: 10.1097/aln.0000000000002865
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Blocks for Ambulatory Shoulder Surgery

Abstract: Background: Nerve blocks improve early pain after ambulatory shoulder surgery; impact on postdischarge outcomes is poorly described. Our objective was to measure the association between nerve blocks and health system outcomes after ambulatory shoulder surgery. Methods:We conducted a population-based cohort study using linked administrative data from 118 hospitals in Ontario, Canada. Adults having elective ambulatory shoulder surgery (open or arthroscopic) from April 1, 2009, to December 31, 2016, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This may be partly explained by the fact that RA patients were far less likely to have received opioid and non-opioid analgesics prior to discharge, and there was no systematic patient education plan in place regarding post-discharge management of the postoperative transition from RA to systemic analgesia. A negative impact of RA (and the associated rebound pain) on healthcare utilization was not however borne out in a much larger retrospective study of over 59,000 patients undergoing outpatient shoulder surgery [52]. Patients who received a PNB, in fact, had a significantly lower rate of unplanned admissions, readmissions, or emergency department visits (9% vs. 12%) in the first seven postoperative days.…”
Section: Healthcare Resource Utilizationmentioning
confidence: 96%
“…This may be partly explained by the fact that RA patients were far less likely to have received opioid and non-opioid analgesics prior to discharge, and there was no systematic patient education plan in place regarding post-discharge management of the postoperative transition from RA to systemic analgesia. A negative impact of RA (and the associated rebound pain) on healthcare utilization was not however borne out in a much larger retrospective study of over 59,000 patients undergoing outpatient shoulder surgery [52]. Patients who received a PNB, in fact, had a significantly lower rate of unplanned admissions, readmissions, or emergency department visits (9% vs. 12%) in the first seven postoperative days.…”
Section: Healthcare Resource Utilizationmentioning
confidence: 96%
“…Hamilton et al, 27 however, did not find increased ED resource utilization among 2207 patients undergoing elective shoulder surgery with and without blocks at their institution, a finding corroborated by their subsequent population study of 59 644 Ontario residents. 4 Liu et al reported that among 103 476 patients undergoing outpatient arthroscopic surgery at 243 facilities in New York state, the most common reason for an unanticipated acute care encounter within 7 postoperative days (ie, inpatient or ED encounter) is musculoskeletal pain (23.8% of the 1867 acute care patient encounters). Similar to our study, these encounters most frequently occurred within the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…3 These benefits have contributed to increasing use of peripheral nerve blocks over time in upper extremity surgery. 4,5 The effect of peripheral nerve blocks on perioperative resource utilization, however, is less clear. It is generally believed that peripheral nerve blocks decrease health care resource utilization by obviating the need for overnight hospital stays for pain control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…86 interestingly, Hamilton et al conducted a multicenter analysis of almost 60.000 patients addressing the issue of peripheral nerve blocks (PNB) for ambulatory shoulder surgery. 87 they compared patients who received peripheral nerve blockade to those who did not about outcomes, such as readmission rates and costs in the first seven days after surgery. They found that "nerve blockade was not associated with any difference in a composite outcome measure, but was associated with a small increase in costs.…”
Section: Regional Anesthesiamentioning
confidence: 99%